2009 IEEE Aerospace Conference 2009
DOI: 10.1109/aero.2009.4839594
|View full text |Cite
|
Sign up to set email alerts
|

Near-field angular distributions of high velocity ions for low-power hall thrusters

Abstract: Abstract-Experimental angular distributions of highenergy primary ions in the near-field region of a small Hall thruster between 50-200 mm downstream of the thruster exit plane at a range of centerline angles have been determined using a highly-collimated, energy-selective diagnostic probe. The measurements reveal a wide angular distribution of ions exiting the thruster channel and the formation of a strong, axially-directed jet of ions along the thruster centerline. Comparisons are made to other experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This is substantially less than the angle change required to produce the high velocity, high angle population seen in experiments. To reproduce the experimental results, one would have to see a change in angle of 60 to 80º [1], [2]. This suggests that another mechanism may be responsible for producing high velocity, high angle ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is substantially less than the angle change required to produce the high velocity, high angle population seen in experiments. To reproduce the experimental results, one would have to see a change in angle of 60 to 80º [1], [2]. This suggests that another mechanism may be responsible for producing high velocity, high angle ions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experimental studies have revealed the presence of high velocity ions at high angles off the centerline in Hall thruster plumes [1], [2]. These ions have kinetic energies that are higher than can be explained by collisional processes such as charge exchange and elastic scattering, and are thought to be ions that have been accelerated through nearly the full acceleration potential of the thruster [3].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal plume divergence angle is determined to be 41.27°, consistent with the experimentally determined angle for the designated magnetic field configuration. Through an extensive survey of literature concerning the SPT-70, the typical range of optimal plume divergence angles is revealed as 44.7°-57.4° [50][51][52][53][54][55]. Specifically, Qian et al mentioned The reproducibility of the genetic algorithm is tested by varying the crossover and mutation rates.…”
Section: Findings and Discoursementioning
confidence: 99%